2006
DOI: 10.1167/6.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Visual search in noise: Revealing the influence of structural cues by gaze-contingent classification image analysis

Abstract: Visual search experiments have usually involved the detection of a salient target in the presence of distracters against a blank background. In such high signal-to-noise scenarios, observers have been shown to use visual cues such as color, size, and shape of the target to program their saccades during visual search. The degree to which these features affect search performance is usually measured using reaction times and detection accuracy. We asked whether human observers are able to use target features to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 30 publications
5
59
0
1
Order By: Relevance
“…For instance, using the method of classification images, Rajashekar, Bovik, and Cormack (2006) found that saccadic target selection was based on structural cues, despite the noisiness of the 1/f displays. Tavassoli, van der Linde, Bovik, and Cormack (2007) continued that line of research, but additionally proposed a variant of the classification image paradigm, with which one can obtain useful classification images in as few as 200 trials.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, using the method of classification images, Rajashekar, Bovik, and Cormack (2006) found that saccadic target selection was based on structural cues, despite the noisiness of the 1/f displays. Tavassoli, van der Linde, Bovik, and Cormack (2007) continued that line of research, but additionally proposed a variant of the classification image paradigm, with which one can obtain useful classification images in as few as 200 trials.…”
Section: Methodsmentioning
confidence: 99%
“…The noise movie was created from a two-dimensional 1/f image (Figure 1)-the same type of image as has been used in other studies (e.g., Geisler et al, 2006;Rajashekar et al, 2006). In those studies, the image was presented statically, but in our present study, it was used as the source for a one-dimensional movie by iterating row-wise through the source image: Each row was stretched vertically in space and presented as a frame ( Figure 2); the movie thus appeared as a flickering bar code.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used classification image analysis (Ahumada and Lovell, 1971;Gold et al, 2000;Eckstein and Ahumada, 2002;Neri and Heeger, 2002;Levi and Klein, 2003;Rajashekar et al, 2006), which allowed us to measure and compare the behaviorally defined, spatial receptive fields of the visual mechanisms responsible for saccadic and perceptual decisions. With this method, the entire brain is viewed as a single system in which input is the stimulus and output is either the saccadic or perceptual decision.…”
Section: Introductionmentioning
confidence: 99%
“…[12] propose how to quantify lost image information and explore a relationship between image information and image quality. The authors of [13] investigated whether observers used structural cues to direct their fixation as they searched for simple embedded geometric targets at very low signal-to-noise ratios; the authors demonstrated that even in case of very noisy displays, observers do not search randomly, but in many cases they deploy their fixation to stimulus regions that resemble some aspect of the target in their local image features. [2] show an evaluation of different recent full reference image quality assessment methods, where they performed a subjective evaluation.…”
Section: The "Reduced-reference" (Rr) Approachmentioning
confidence: 99%